Da leitura à escrita: o gênero crônica na perspectiva do letramento literário na EJA - Silva, Camila Maria de Menezes (2023)
The teaching of literature in schools often confines itself to fragmented practices, limited to the knowledge of isolated texts, authors, and their respective works. In the context of elementary education, classroom reading has been restricted to the content of the textbook, with activities focused solely on the search for grammatical information in the text, without allowing students to develop their reading skills. In most cases, students read only to obtain specific answers related to the proposed exercises. These practices have contributed to further alienating students from reading, as they do not perceive the importance of this act. Additionally, the lack of reading results in significant difficulties in writing. For reading to be seen as a meaningful practice for students, it is necessary for it to be approached differently from these often still adopted practices today. It is of paramount importance that students perceive reading as an enjoyable and meaningful activity. With this goal in mind, and recognizing the need to reform literature education, especially in the context of Adult Education (EJA), this project aims to introduce the practice of literary chronicles as a tool to promote literary literacy. The intention is to effectively integrate literary reading and writing into the teaching and learning process. This study adopts a descriptive approach with bibliographical grounding and a propositional methodology. Through the contributions of renowned authors such as Cosson (2020), Dalvi (2013), Kleiman (2008), Lajolo (2018), Machado (1994), Sá (1985), Terra (2018), among others, we seek to understand the challenges faced in the teaching of literature, specifically regarding literary literacy in schools. As a result, we have developed a pedagogical handbook with activities aimed at fostering students' comprehension, interpretation, written and oral expression, including the careful selection of literary chronicles suitable for the EJA audience.